Spatial issues revisited: A note on the role of shared transportation modes - Marion Drut (European Regional Science Association (ERSA), 2016)
Spatial and environmental issues related to mobility are exacerbated in urban areas. Road congestion, rivalry of use for parking spaces and air pollution are major issues regularly at the heart of local transportation policies. They have been dealt with through various approaches. Mass transit have recently been fostered as a solution against road congestion and rivalry of use. These spatial issues relate to the space consumed by transportation modes. Private cars are assumed to consume larger quantities of space than mass transit, while offering similar services, namely origin-to-destination trips. Similarly, cars are the most polluting mode and transportation policies fostering bicycles have thrived in order to reduce air pollution, in particular CO2, and NOX emissions and PM. However, private cars remain the leading transportation mode for commuting trips (except in some large cities, such as Paris where mass transit is the leading mode). On the contrary, shared modes such as taxis, car-sharing and self-service cars or bicycles are often overlooked in transportation policies. In this article, I focus on shared modes, namely vehicle-sharing and self-service vehicles. The contribution is twofold. First, I explore the mechanisms through which shared modes help reduce road congestion and rivalry of use for parking spaces, as well as air pollution, compared to private modes. Second, I highlight the fact that transportation modes do not provide similar services to users. Therefore, gross comparisons in terms of time-space consumptions between modes (Marchand, 1993) are oversimplifying. I suggest to put these gross estimations into perspective accounting for additional services provided by transportation modes. Refined measures of time-space consumptions are presented. When the service provided is accounted for, the gap between mass transit and private cars is reduced. More importantly, the results show that car-sharing and self-service cars constitute relevant alternatives to private cars in terms of time-space consumption per unit of service provided. The analysis provides guidelines for decision-makers since it clearly indicates orders of magnitude for time-space consumptions from various transportation modes. The study reveals that both types of shared modes help reduce spatial and environmental issues related to mobility in urban areas and as such constitute key components of a comprehensive and efficient transportation system. For instance, I demonstrate that shared low-carbon modes, such as self-service bicycles, have the potential to reduce simultaneously both spatial (congestion and rivalry of use) and environmental (air pollution) issues in medium-sized city. Furthermore, I mention the limits of the present organization for shared modes. More precisely, the need for institutionalizing is highlighted for car-sharing, and network expansion required for self-service vehicles.
Keywords: D6; D61; Q28; Q30; 330; mobility; shared modes; spatial issues; time-space consumption